2014
DOI: 10.1098/rspb.2013.2881
|View full text |Cite
|
Sign up to set email alerts
|

A well-constrained estimate for the timing of the salmonid whole genome duplication reveals major decoupling from species diversification

Abstract: Whole genome duplication (WGD) is often considered to be mechanistically associated with species diversification. Such ideas have been anecdotally attached to a WGD at the stem of the salmonid fish family, but remain untested. Here, we characterized an extensive set of gene paralogues retained from the salmonid WGD, in species covering the major lineages (subfamilies Salmoninae, Thymallinae and Coregoninae). By combining the data in calibrated relaxed molecular clock analyses, we provide the first well-constra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
496
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(519 citation statements)
references
References 53 publications
(126 reference statements)
21
496
1
1
Order By: Relevance
“…3b; Extended Data Fig. 2c and Supplementary Information section 6), in agreement with recent age estimates 8,13 . Interestingly, analysis of asymmetry in coding sequence evolution between homeologues showed that a major part of the sequence divergence happened since the Salmo-Oncorhynchus split, suggesting a considerable temporal decoupling between the Ss4R event and sequence divergence of the Ss4R duplicates (Supplementary Information section 6).…”
Section: Post-ss4r Rediploidization Characteristicssupporting
confidence: 86%
See 1 more Smart Citation
“…3b; Extended Data Fig. 2c and Supplementary Information section 6), in agreement with recent age estimates 8,13 . Interestingly, analysis of asymmetry in coding sequence evolution between homeologues showed that a major part of the sequence divergence happened since the Salmo-Oncorhynchus split, suggesting a considerable temporal decoupling between the Ss4R event and sequence divergence of the Ss4R duplicates (Supplementary Information section 6).…”
Section: Post-ss4r Rediploidization Characteristicssupporting
confidence: 86%
“…Very little is known about the mechanisms of genomic and chromosomal reorganization after WGD in vertebrates because the 1R, 2R and Ts3R occurred so long ago that few clear signatures of post-WGD reorganization events remain. In contrast, a fourth WGD (the Ss4R salmonid-specific autotetraploidization event) occurred in the common ancestor of salmonids ~80 Mya after their divergence from Esociformes ~125 Mya [6][7][8] (Fig. 1), and the continued presence of multivalent pairing at meiosis and evidence of tetrasomic inheritance in salmonid species suggests that diploidy is not yet fully re-established 6,9,10 .…”
mentioning
confidence: 99%
“…Genetic differentiation between Norwegian populations was reported earlier 15 and the Alta population aligns close to those populations. Current thinking is that the diversification among salmonid species and genetic isolation due to anadromy might be connected to climatic cooling during recent ice ages 16 . Moreover, the prevalence of local adaptations increases with geographical distance 17 , which led us to expect local adaption for the Alta population, where the river temperature has not increased above 18°C for at least the last 30 years, and the Dordogne population, which regularly encounter temperatures over 20°C in their natural habitat.…”
Section: Discussionmentioning
confidence: 99%
“…These similarities led Schranz et al to propose that a temporal delay between WGD and radiation is a pattern generally observed and called it "time-lag model" (Schranz et al, 2012). Also in salmonids, a gap of 40-50 million years between WGD (which likely took place 88-103 mya) and diversification (although low in comparison to some other teleost groups) was reported (Macqueen and Johnston, 2014).…”
Section: State Of Evidence For Ts-wgd Causing Evolutionary Success Anmentioning
confidence: 99%